2004
DOI: 10.1177/0363546503261700
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone Decanoate and Load Increase Remodeling and Strength in Human Supraspinatus Bioartificial Tendons

Abstract: Data suggest anabolic steroids may enhance production of bioartificial tendons and rotator cuff tendon healing in vitro. More research is necessary before such clinical use is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 57 publications
1
45
0
3
Order By: Relevance
“…A recent in vivo study reported AAS treatment can impair Achilles' tendon remodeling by down-regulating matrix metallopeptidase activity, and thus increase the potential for injury [47]. In an in vitro rotator cuff tendon model, human supraspinatus tenocytes treated with nandrolone decanoate and subjected to mechanical load had more organized actin cytoskeleton and increased collagen matrix remodeling and mechanical properties [68]. More research is required to determine the effect of AASs on tendon healing, but this was the first known study to document the acute effect of anabolic steroids on human rotator cuff tendon cells.…”
Section: Effect Of Anabolic-androgenic Steroids On Tendon-bone Healingmentioning
confidence: 98%
“…A recent in vivo study reported AAS treatment can impair Achilles' tendon remodeling by down-regulating matrix metallopeptidase activity, and thus increase the potential for injury [47]. In an in vitro rotator cuff tendon model, human supraspinatus tenocytes treated with nandrolone decanoate and subjected to mechanical load had more organized actin cytoskeleton and increased collagen matrix remodeling and mechanical properties [68]. More research is required to determine the effect of AASs on tendon healing, but this was the first known study to document the acute effect of anabolic steroids on human rotator cuff tendon cells.…”
Section: Effect Of Anabolic-androgenic Steroids On Tendon-bone Healingmentioning
confidence: 98%
“…The existing studies are related to the following tissue engineering methodologies: gene transfer, in situ tissue engineering and in vitro production of bioengineered tendons. We obtained 15 experimental papers and, in more detail, 4 papers on gene therapy [11][12][13][14], 9 papers on in situ tissue engineering with the use of bioactive acellular membranes [6,[15][16][17][18][19][20][21][22] and 2 papers on in vitro tissue engineered tendons [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…More than 300,000 operations are performed each year for the reconstruction of the rotator cuff in the USA, more than 30% of rotator cuff tears may be of difficult treatment or beyond repair and failure rates after primary repair have been reported to be 13%-68% for open repairs [2,5]. Revision rotator cuff surgery has also been shown to have less successful outcomes than primary repairs [6]. Tissue engineering may play a major role in the treatment of these injuries through replacement of an injured tendon segment [7].…”
Section: Introductionmentioning
confidence: 99%
“…21 However, so far, few studies have been done on rotator cuff tendon regeneration by means of in situ tissue engineering and in vitro bioengineering of tendons as compared to the extensive work on bone and cartilage. 6,14,[22][23][24][25] This previous literature review, showed the necessity for future studies in this area, and, therefore, an in vitro study was performed by isolating tenocytes from the rotator cuff of normal and GC-treated rats. The tenocytes were cultured on two collagenous membranes and cell proliferation and function were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…1 More than 30% of rotator cuff tears may be difficult to treat or beyond repair, failure rates after primary repair have been reported to be 13% to 68% for open repairs and revision rotator cuff surgery has been shown to have less successful outcomes than primary repairs. 1,5,6 Tissue engineering may play a major role in the treatment of these injuries through replacement of an injured tendon segment. 7 Tendons are arguably the least complex of the connective tissues with respect to their composition and architecture and this leads to the expectation that they would be more amenable to tissue-engineered approaches than other tissues.…”
Section: Introductionmentioning
confidence: 99%